Diversity in women and their vaginal microbiota - Condori Catachura, Sandra (2025)
Women’s health is essential to global societal and economic wellbeing, yet health disparities remain prevalent. The vaginal microbiota plays a critical role in health, with research indicating that reduced levels of core bacteria, such as lactobacilli, are associated with conditions like bacterial vaginosis (BV) and in-creased infection susceptibility. Lower levels of vaginal lactobacilli are reported more frequently in women of African and Latin American descent compared with women of European and Asian descent. However, geographical and other study inclusion and analysis biases influence current research. This opinion highlights the need for a more comprehensive understanding of a ‘healthy’ vaginal microbiome. It underscores efforts to broaden global research on microbiome di-versity in socially relevant contexts, avoiding inappropriate applications of terms such as race and ethnicity.